2020
DOI: 10.21203/rs.3.rs-92513/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent Rhodium-Catalyzed Electrochemical Vinylic C–H Annulation of Acrylamides with Alkynes

Abstract: A Rh-catalyzed electrochemical vinylic C–H annulation of acrylamides with alkynes has been developed in an undivided cell, affording cyclic products in good to excellent yield. Divergent syntheses of α-pyridones and cyclic imidates are accomplished by employing N-phenyl acrylamides and N-tosyl acrylamides as substrates, respectively. Additionally, excellent regioselectivities are achieved when using unsymmetrical alkynes. This electrochemical process is environmentally benign compared to traditional transition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…9,[27][28][29][30] To the best of our knowledge, the coupling reaction between simple alkenyl ligands and external alkynes has been unexplored heretofore. On the other hand, the coupling of alkynes with alkenyl molecules is of ultimate relevance in metal-mediated organic synthesis, [31][32][33][34][35][36] and the alkyne insertion into metal-alkenyl bonds constitutes a key step of the important Dötz reaction. [37][38][39] We selected the diruthenium complex [Ru 2 Cp 2 (CO) 2 (μ-CO) {μ-η 1 :η 2 -C(Ph)vCH(Ph)}]BF 4 , [1]BF 4 , as a convenient starting material to provide a chance for the μ-alkenyl-alkyne coupling; Knox and co-workers previously demonstrated that complexes homologous to [1]BF 4 , bearing different alkenyl substituents, display a versatile chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…9,[27][28][29][30] To the best of our knowledge, the coupling reaction between simple alkenyl ligands and external alkynes has been unexplored heretofore. On the other hand, the coupling of alkynes with alkenyl molecules is of ultimate relevance in metal-mediated organic synthesis, [31][32][33][34][35][36] and the alkyne insertion into metal-alkenyl bonds constitutes a key step of the important Dötz reaction. [37][38][39] We selected the diruthenium complex [Ru 2 Cp 2 (CO) 2 (μ-CO) {μ-η 1 :η 2 -C(Ph)vCH(Ph)}]BF 4 , [1]BF 4 , as a convenient starting material to provide a chance for the μ-alkenyl-alkyne coupling; Knox and co-workers previously demonstrated that complexes homologous to [1]BF 4 , bearing different alkenyl substituents, display a versatile chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…As an important tool of constructing chemical bonds, electrosynthesis uses electrons as reagents to implement the redox reaction. [32][33][34][35][36][37][38][39][40][41][42][43] Although there has been a lot of research on the electrochemical C-H activation reaction of alkenes [44][45][46][47][48][49] or alkynes, [50][51][52][53][54] the reactions in which allenes are involved have rarely been reported. So far, only Ackermann's group has reported two electrochemical C-H activation reactions using allene as substrate via cobalt catalyst 55,56 (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, rTMS has had widespread usage as a non-invasive neuromodulation technique for treating various conditions, including PD, stroke, depression, and other neuropsychiatric disorders (Guo et al, 2017;Dionísio et al, 2018;Latorre et al, 2019;Leung et al, 2020). While several studies both domestically and internationally, have reported the effects of motor cortex rTMS on motor symptoms of PD (Chou et al, 2015;Yang et al, 2018;Latorre et al, 2019), only two clinical reports exist regarding the use of FOGQ as an observation index for assessing the impact of M1 rTMS on FOG in PD (Rektorova et al, 2007;Kim et al, 2015). Rektorova et al (2007) were among the first to report on the efficacy of rTMS for alleviating FOG symptoms in PD patients using a cross-over experimental design.…”
Section: Discussionmentioning
confidence: 99%